Problem-based Learning in Basic Physics– X - Mody, A.K.; Pradhan, H. C. (SCHOOL SCIENCE, 2016)
In this article (10th in the PBL series) we consider various examples from different areas of physics where we have systems in which one of the parameter varies continuously and to estimate any effect we need to take differential element and perform integration separately (different from that which is already performed in arriving at standard textbook formula).